The mediation path of physical multimorbidity on the vulnerability to health-related poverty of rural aging families in Ningxia, China: A cross-sectional survey - Guo, Wenqin; Du, Jiancai; Chen, Kexin; Wang, Wenlong; Gao, Baokai; Hu, Zhaoyan; Qiao, Hui (Frontiers in Public Health, 2022)
Abstract Background: Vulnerability to health-related poverty can predict the probability of families falling into poverty due to health risk impact. In this study, we measured the vulnerability to health-related poverty and examined the mediation path of physical multimorbidity on the vulnerability to health-related poverty of rural aging families in Ningxia,China. Methods: This cross-sectional study was conducted in Ningxia, China, in February 2019. A multi-stage stratified cluster-randomized design was used to obtain a representative sample in each county.We included participants aged 60 years and older,who had lived there for more than one year.A total of 3653 rural residents older than 60 years old were selected as the research subjects.The three-stage generalized least square method was used to calculate the expected vulnerability to poverty.We used mediating effect model to test the mediation path of poverty vulnerability related to the physical multimorbidity. Results: Under different poverty line standards, i.e., 1.9/day as low vs. 3.1/day as the high poverty line, the proportion of families that could fall into poverty in the future was 5.3% and 53.7%, respectively. The prevalence of chronic diseases and physical multimorbidity among rural residents >60 years old was 64.62% and 21.24%, respectively.The results of mediating effect test showed that self-rated health status(indirect effect a*b=-0.0052), non-agricultural employment(a*b=-0.0046), household cattle production(a*b=0.0004),housing type (a*b=-0.0008), gift expenses (a*b=0.0006)and loan for illness(a*b=0.0034)were the mediation paths of poverty vulnerability related to the physical multimorbidity. Conclusions: Concerted efforts are needed to reduce poverty vulnerability related to the physical multimorbidity. The strategy of alleviating poverty should emphasis on promoting non-agricultural employment of vulnerable groups sustainability and developing rural economy, which are important paths to reduce family’s vulnerability to health-related poverty.